Remdesivir-Induced Hepatotoxicity: A Systematic Review of Clinical Evidence, Pharmacokinetics, and Safety Concerns - Hamdan, Angkasa Ramatuan; Bestari, Muhamad Begawan; Girawan, Dolvy; Agustanti, Nenny; Husain, Okky; Hasan, Nadeem S. (The Indonesian Society for Digestive Endoscopy, 2025)
Background: Remdesivir is widely used for the treatment of COVID-19, with its potential benefits currently under investigation. Concerns remain regarding its potential hepatotoxic side effects. Drug-drug interactions, specifically with CYP3A4 and P-glycoprotein inhibitors, may worsen hepatotoxicity. In this context, dexamethasone has been suggested to mitigate liver injury, but the role remains unclear. Therefore, this study aimed to explore the characteristics, mechanisms, and risk factors of remdesivir-induced hepatotoxicity through a systematic review of case reports.Methods: A systematic review was conducted using databases such as PubMed, Scopus, EBSCO, and BMJ Case Reports for cases published from 2020 to 2024. The keywords used were “remdesivir,” “hepatotoxicity,” “COVID-19,” and “liver failure.” Relevant case reports were selected based on predefined inclusion and exclusion criteria. Furthermore, data were extracted following the Joanna Briggs Institute (JBI) checklist for case reports.Results: Among 46 individual articles screened after the removal of duplicates, five that detailed a total of six patients were eligible for inclusion. Hepatotoxicity was frequently reported in elderly patients and those with chronic liver disease. Drug-drug interactions that include remdesivir and CYP3A4 inhibitors increased the risk of liver injury. Based on observation, dexamethasone was associated with reduced hepatotoxicity, primarily due to its anti-inflammatory effects. In patients with ALT 5× ULN, remdesivir administration was controversial. Some cases showed improvement, and others required discontinuation due to severe liver dysfunction.Conclusion: This study emphasized the necessity for safety evaluations and standardized liver function monitoring in patients receiving remdesivir. Further investigation is essential to define clinical guidelines and improve patient safety in antiviral treatments.